Physiological and physico-chemical changes during ripening of 'Legaspi Special' red-orange strain papaya (carica papaya L.) - Bulaong, Sonia SP.; Acevedo, Teresita P. (2002.)
The objective of this study was to characterize the physiological and physicochemical changes during ripening at ambient conditions of 'Legaspi Special' red orange strain papaya cultivated in Guinobatan, Albay. The influence of the stage of maturity at harvest on the physicochemical characteristics of ripened fruits was also determined. papayas harvested a mature green and color break stages and ripened at ambient conditions were not significantly different in terms of pH, % titrable acidity, % total soluble solids and fresh firmness. Based on t-test, the fruits differed only in the number of days required to reach table ripe stage. On the average, fruits harvested at color break stage ripened within four (4) days. Differences in sensory qualities of flesh color, texture and taste were noted but not quantified due to sample limitation. Physiological and physicochemical changes during ripening were monitored using fruits harvested at mature green stage. Fully mature fruits ripened within six (6) days while less mature fruits ripened within or eleven days after harvest. The peak of carbon dioxide production at peel color index 3 (more green than yellow) preceeded the ethylene peak which occurred at peel color index 4 (more yellow than green). Ripening, as indicated by change in flesh color, started in tissues surrounding the fruit cavity when internal ethylene was 0.03-0.06 ppm during the preclimacteric stages at peel color indices 1 and 2 (mature green and color break stages, respectively). Linear regression indicated that both the increase in yellow peel color and the decrease in fruit firmness correlated highly with changes in internal ripening such as decrease in pH, increase in % titrable acidity, increase in water-soluble pectins and decrease in acid soluble pectins. The decrease in pH correlated significantly with increase in % titrable acidity and increase in % TSS. The increase in ascorbic acid up to 51.9% mg% did not correlate with increase in % titrable acidity in this fruit. Beta carotene increased 5-fold at table ripe stage to 5.60 ug/g fresh weight.
Thesis (M.S.Food Science)--University of the Philippines, Diliman.
Keywords: Papaya -- Philippines -- Albay; Papaya -- Postharvest physiology -- Philippines -- Albay; Fruit -- Ripening